Corruption begins in the electoral process (2019)
The way to exercise politics must rethink, the Colombian people have the obligation to understand how the sociopolitical structure of the country works, its rights and obligations as citizens. It will not be easy, but it can be achieved, it will be everyone's work that depends to a large extent on teaching in the classrooms and on the values that are instilled in the family as the most important nucleus of every society. The hypothesis is then raised that in the electoral process is where corruption begins. "Corruption can occur in a variety of ways in an electoral democracy. Probably one of the most well-known acts of corruption is to sell the vote during the elections to acquire some necessary resource for the families or for some interest that the candidate can fill if he is elected (Medellín Torres, 2014, pp. 505).